2015
DOI: 10.12777/wastech.3.1.22-26
|View full text |Cite
|
Sign up to set email alerts
|

Jatibarang Final Solid Waste Dumping Site of Semarang City and Its Problems

Abstract: -Solid waste is big problem in most cities in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…River water supplies are essential for household human uses like drinking, cooking, and washing, even if they are mostly utilized for agricultural irrigation. Many studies found that river water pollution in the tropical region was significantly contributed by land development activities such as agricultural activities and population settlements [2] [3] [4] [5], waste and heavy metal disposal from industrial activities [2], landfill areas [6] [7], extraction and mining industry [8], and domestic rubbish disposal [4] [9] [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…River water supplies are essential for household human uses like drinking, cooking, and washing, even if they are mostly utilized for agricultural irrigation. Many studies found that river water pollution in the tropical region was significantly contributed by land development activities such as agricultural activities and population settlements [2] [3] [4] [5], waste and heavy metal disposal from industrial activities [2], landfill areas [6] [7], extraction and mining industry [8], and domestic rubbish disposal [4] [9] [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although river resources are primarily used for agricultural irrigation, they are still important for domestic human needs such as water to drink, cooking, and washing. Many studies have shown that land development activities cause significant river pollution in these tropical regions through the development new agricultural areas, population settlements [2,[5][6][7], industrial waste discharge and heavy metals disposal [3,7,8] landfill areas [9,10], mining activities [1], and domestic waste disposal such as rubbish [5,11,12].…”
Section: Introductionmentioning
confidence: 99%